Komunikasi Partisipatif pada Sekolah Lapangan Pengelolaan Tanaman Terpadu (SL-PTT) - Karmila Muchtar; Ninuk Purnaningsih; Djoko Susanto (Institut Pertanian Bogor, 2014)
ABSTRACTField School of Comprehensive Agriculture Land-Use Management (SL-PTT) is agricultural innovation system mainly directed to improve production of rice applying bottom-up and participative communication approach of the farmers. The study aims to get descriptions on how participative communication can be applied on the SL-PTT program and to analyze decision making process by the farmers to adopt and utilize the technology of rice innovation in their land -use. The study was planned using survey descriptive correlation. The study was done on March-April 2014 covered 80 farmers as respondents who involved in SL-PTT program. Data and hypothesis were analyzed and tested using multiple linear regression. The evidence showed that participative communication of the farmers toward SL-PTT program was considerable good although they are not in entire program steps. The steps of the PRA and field meeting, activation of farmers in dialogue session is grouped to low by 5% and 12,5%. While in the routine meeting and daily discussion, it is categorized as high, i.e 78,7% and 96,3% because the interaction of the extension worker and the farmers is considerable active. The respect of the extension worker was also supporting. Almost all (91,25%) of the farmers applied all innovations, such as: using high qualified seeds, planting system, using appropriate fertilizer and water irrigarion, controlling pests, harvest and past-harvest management. Factors which have significant effect on applying participative communication are: farmer’s characteristics, characteristics of the extension worker and forum of communication between the extension worker and the farmers.Keywords: Communication, Innovation, Partisipative, SL-PTT